Potential Development Management of Students in Islam - MOCH CHARIS HIDAYAT; CHOIRUL MAHFUD (Ta'dib: Jurnal Pendidikan Islam, 2019)
This study aimed to investigate and describe the management of developing potential students based on Islamic views. This study used a qualitative method with a case study approach. The subjects of the research were Madrasah supervisors, Madrasah headmasters, and the teachers. The results of the study showed that the development of potential students when referring to the objectives of national education in particular and development, in general, is to create "Total Man" by creating human beings who has complete characteristics, harmonious, and balanced in the development of all aspects of his personality. Humans as a whole are individuals who can reach all relationships with God, with the environment or natural surroundings, with other humans in a constructive social life and with themselves. Management of the development of potential students based on Islamic views stipulates that new education will end when someone dies. Physically, seeking knowledge will end when someone dies, but the process of seeking knowledge continues to an infinite limit.